2011
DOI: 10.1016/j.ibmb.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in acetyl-CoA carboxylase and fatty acid synthase 1 differentially affect eggshell formation and blood meal digestion in Aedes aegypti

Abstract: To better understand the mechanism of de novo lipid biosynthesis in blood fed Ae. aegypti mosquitoes, we quantitated acetyl-CoA carboxylase (ACC) and fatty acid synthase 1 (FAS1) transcript levels in blood fed mosquitoes, and used RNAi methods to generate ACC and FAS1 deficient mosquitoes. Using the ketogenic amino acid 14C-leucine as a metabolic precursor of 14C-acetyl-CoA, we found that 14C-triacylglycerol and 14C-phospholipid levels were significantly reduced in both ACC and FAS1 deficient mosquitoes, confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 22 publications
4
66
1
Order By: Relevance
“…B. terrestris FAS (GenBank accession number: JN982132) shares 96 % sequence identity with the predicted FAS from Bombus impatiens, 75 % identity with the predicted FAS from A. mellifera, and 55 % identity with a previously characterized FAS from Aedes aegypti. [41] We detected an increasing level of B. terrestris FAS transcripts in LG from pharate imago up to three days old. There was a modest decrease in LG FAS transcript level in five-day-old bumblebees.…”
Section: Relative Quantification Of Fatty Acid Synthase Transcript Lementioning
confidence: 71%
“…B. terrestris FAS (GenBank accession number: JN982132) shares 96 % sequence identity with the predicted FAS from Bombus impatiens, 75 % identity with the predicted FAS from A. mellifera, and 55 % identity with a previously characterized FAS from Aedes aegypti. [41] We detected an increasing level of B. terrestris FAS transcripts in LG from pharate imago up to three days old. There was a modest decrease in LG FAS transcript level in five-day-old bumblebees.…”
Section: Relative Quantification Of Fatty Acid Synthase Transcript Lementioning
confidence: 71%
“…ACC-deficient mosquitoes produce defective oocytes that lack intact eggshells and give rise to nonviable eggs [24]. One explanation for the observed defect in eggshell formation in ACCdeficient mosquitoes is that de novo fatty acid biosynthesis in ovary tissues is required to generate the lipid components of the eggshell [25].…”
Section: Expression Profiling Analysis Between Sr and Ss Transcriptommentioning
confidence: 99%
“…It has been demonstrated that fatty acid synthase (FAS) plays a central role in lipid accumulation in both vertebrates and invertebrates91011. FAS regulates de novo lipogenesis by converting acetyl-CoA into palmitate, leading to the production and storage of triacylglyceride (TG)12.…”
mentioning
confidence: 99%
“…Upregulation of FAS was observed during early diapause in the mosquito Culex pipiens 1314 and knockdown of FAS1 reduced lipid accumulation and affected the overwintering survival of females of this species15. FAS has also been found to promote lipid accumulation in another mosquito Aedes aegypti 9. It is now generally accepted that FAS regulates lipid accumulation in insect diapause.…”
mentioning
confidence: 99%